Assessing the Sharia Compliance of Hotel Facilities and Services in East Java: A Comparative Analysis of National and International Standards - Rahmawati, Lilik; Pratikto, Muhammad Iqbal Surya; Wigati, Sri; Muflihin, Muhammad Dliyaul; Rahmani, Nur Maulidah Dini; Muntazeri, Eliya Najma (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2025)
This study aims to examine the compliance of Sharia-compliant hotels in East Java, Indonesia, with both national standards (DSN-MUI Fatwa No. 108/2016) and international benchmarks (CrescentRating and Salam Standard). Utilizing a qualitative methodology involving field observations and semi-structured interviews across three hotels—Namira Syariah Surabaya, Radho Syariah Malang, and Walan Syariah Sidoarjo—the research reveals partial yet consistent alignment with core Sharia hospitality principles. These include the prohibition of immoral activities, availability of prayer amenities, and the absence of alcohol and gambling. However, the integration of Islamic financial institutions remains absent across all hotels, indicating a gap in full Sharia compliance as defined nationally. From an international perspective, all hotels meet the